2022
DOI: 10.1002/slct.202104114
|View full text |Cite
|
Sign up to set email alerts
|

SO2F2‐Promoted Dehydroxylative Fluorination of Alcohols

Abstract: Reported here is the development of a novel, mild and practical protocol for the SO2F2‐promoted dehydroxylative fluorination of readily available alcohols. The advantages of this protocol include an inexpensive and available reagent, and operational simplicity. This method enables the transformation of many kinds of primary, secondary and tertiary (hetero) arene alcohols into the corresponding fluorides and tolerates a range of functional groups. And the reactions occur smoothly to give the desired products in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…In 2014, Sharpless and colleagues reported a method for the rapid synthesis of aryl fluorosulfonates (which played an important role in sulfur­(VI) fluoride exchange (SuFEx) click chemistry) by the reaction of phenols and SO 2 F 2 under mild conditions . Recently, the Sanford group and our group have successively reported SO 2 F 2 -promoted deoxyfluorination of phenolics, α-ketoesters, and alcohols. Our group has been working on the application and development of sulfuryl fluoride and found that sulfuryl fluoride can not only deoxygenate but also act as a potential fluorination and oxidation reagent.…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Sharpless and colleagues reported a method for the rapid synthesis of aryl fluorosulfonates (which played an important role in sulfur­(VI) fluoride exchange (SuFEx) click chemistry) by the reaction of phenols and SO 2 F 2 under mild conditions . Recently, the Sanford group and our group have successively reported SO 2 F 2 -promoted deoxyfluorination of phenolics, α-ketoesters, and alcohols. Our group has been working on the application and development of sulfuryl fluoride and found that sulfuryl fluoride can not only deoxygenate but also act as a potential fluorination and oxidation reagent.…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, our group published a mild method for the dehydrofluorination of multiple (hetero)aromatic alcohols involving the generation and elimination of key sulfonyl ester intermediates. [29] We became interested in extending this strategy to a wider range of substrates and to all halogens. Hence, based on our preliminary results and the special properties of SO 2 F 2 , we established new conditions, featuring SO 2 F 2 , NH 4 X, (X = F, Cl, Br, or I), and a base, toward achieving the aforementioned synthetic goal (Scheme 1(3)).…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Sammis's group [28] reported SO 2 F 2 ‐mediated alcohol substitution and deoxygenation through the conversion of fluorosulfates to alkyl halide intermediates. In 2022, our group published a mild method for the dehydrofluorination of multiple (hetero)aromatic alcohols involving the generation and elimination of key sulfonyl ester intermediates [29] . We became interested in extending this strategy to a wider range of substrates and to all halogens.…”
Section: Introductionmentioning
confidence: 99%
“…It involves displacing an activated alcohol by a fluoride ion, which is especially challenging on hindered centers. Fluorination techniques are usually carried out with Selectfluor, HF salts such as Et 3 N·3HF and Olah’s reagent (pyridine·9HF), or S–F bond-type reagents (DAST, SF 4 , Deoxo-Fluor, Pyfluor) . However, the handling of those reagents can require additional considerations.…”
mentioning
confidence: 99%
“…Fluorination techniques are usually carried out with Selectfluor, HF salts such as Et 3 N•3HF and Olah's reagent (pyridine•9HF), or S−F bond-type reagents (DAST, SF 4 , Deoxo-Fluor, Pyfluor). 9 However, the handling of those reagents can require additional considerations. Selectfluor displays poor solubility in organic solvents; 10 HF salts often require high temperatures to be effective, 2 and the higher the amount of HF, the higher the risk for the user.…”
mentioning
confidence: 99%